Efecto del uso del suelo sobre indicadores del estado de la calidad del suelo en áreas cañeras de la CPA “Batalla de Santa Clara” - Oumarou Mahamane, Ismael (Universidad Central "Marta Abreu" de Las Villas, 2015)
For evaluating the effect of land use on the state of soil quality, there were selected a natural ecosystem as reference pattern, and one sugar cane area (CPA “Batalla de Santa Clara”) both on a Brown calcareous soil. The work was developed between December, 2012 and December, 2014. Both ecosystems were characterized and three composite samples were taken to a depth of 0-20 cm with the purpose of determining a physical indicators (AE, FE, LIP, LSP, IP, permeability) chemical pH(H2O), pH(KCl), MO, P2O5 and K2O) and biological of the soil (Quantification of bacteria, fungi, actinomicetes) and of the mesofauna (mites and collembolans). The results of these analyses were processed in the statistical package STATGRAPHICS version 5.0 on Windows 7 by means of One-way Anova and an analysis of the main components with the chemical and biological indicators. The results demonstrated that the natural ecosystem had a good stability while the sugar cane area had been managed conventionally with a low-level of inputs and mechanization. In both ecosystems the soil had a good structure and physical state. The pH showed significant differences between both ecosystems. The levels of organic matter were superior in the natural ecosystem in comparison with the sugar cane areas that reported contained low levels. The microbial populations of the actinomicetes and the fungi were more marked then in the bacteria. There was higher diversity of the fungi iden-tified in the natural ecosystem. From the analysis of the main components conclusion was made that the microbiological indicators and of the mesofauna had a biggest weight in the differentiation of the studied ecosystems that the chemical indicators.
Keywords: Suelos; CPA “Batalla de Santa Clara”